KEANEKARAGAMAN TUMBUHAN PAKU TERESTRIAL DI HUTAN KOTA DKI JAKARTA - Dwi Andayaningsih; Tatik Chikmawati; Sulistijorini Sulistijorini (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Urban forest is one of the green open area consisted of natural forest-like vegetation. It has suitable microclimate for understory habitat, including terrestrial ferns. The diversity of fern in three urban forest in DKI Jakarta is reported, i.e the urban forest at The University of Indonesia (UI) Campus, The Cibubur Arboretum and PT JIEP (Jakarta Industrial Estate Pulogadung). Vegetation analysis was conducted by purposive sampling method with a transect line of 200 m in each location with 15 plots of (3x3) m2 each. Fern determination was done based on herbarium specimens and literatures. Fern diversity was analyzed based on Shannon diversity index, and equality index. Canonical correspondence analysis (CCA) was performed to determine the correlation between fern diversity and abiotic factors. There were 18 fern species classified into 11 genera and eight families, at the UI urban forest and Cibubur Arboretum, but there was no fern in PT JIEP. Fern with the highest importance value index was Sphaerostephanos sp. (161.33%) in The UI urban forest, and Lygodium microphyllum (Cav.) R.Br. (71.63%) in Cibubur Arboretum. The CCA result showed that the fern diversity correlated to four abiotic factors i.e temperature,humidity, light intensity and soil pH.